Traditional Chinese Medicine nursing for patients with skin rash caused by pegylated interferon α-2a combined with ribavirin therapy of chronic viral hepatitis C (慢性丙型肝炎患者聚乙二醇干扰素α-2a联合利巴韦林抗病毒治疗所致皮疹的中医护理体会) - LI Hongyan (李红艳); WANG Xiaojun (汪晓军); ZHANG Lili (张莉莉) (中西医结合护理)
This paper analyzed the clinical data of 5 patients with skin rash caused by pegylated interferon α-2a combined with ribavirin therapy of chronic viral hepatitis C. According to the clinical symptoms, patients were given internal administration of Chinese herbal medicine decoction combined with external wash of Chinese herbal medicine decoction. Comprehensive interventions including skin care, infection prevention, nutrition support and psychological nursing were carried out during the treatment. (本文回顾聚乙二醇干扰素α-2a联合利巴韦林抗病毒治疗慢性丙型肝炎过程中出现皮疹(斑丘疹型)的5例患者的临床资料, 总结相关护理措施。结合患者中医证候表现, 辨证给予中药汤剂内服联合中药汤剂外洗患处, 同时配合实施皮肤护理、预防感染、营养支持、心理护理等措施。)